The Internationalization of Higher Education: The contribution of the new Moroccan strategy Pact ESRI/ HERI 2030 to enhance mobility - LAMDAGHRI , Nihal; NAIT BELAID , Youssef; VON KORFLESCH , Harald; ZEBAKH , Sanaa (Revue Internationale des Sciences de Gestion, 2024)
Nowadays, the need for international cooperation and knowledge exchange is increasingly crucial in a world characterized by constant change and progress. To enhance education, develop suitable study programs, and enable students, professors, and researchers to improve their profiles, the concept of internationalizing the higher education system has evolved. In Morocco, the Pact ESRI/HERI 2030 focuses on various projects aimed at promoting the internationalization of higher education. This research seeks to understand the significance of internationalization and its impact on the Moroccan higher education system, particularly regarding the international mobility of students. It aims to evaluate how the Pact ESRI/HERI 2030 can serve as a lever for this internationalization. The empirical aspect of the study examines the motivations, constraints, and effects of international student mobility on individuals and the multicultural values it fosters. Utilizing qualitative and quantitative research methods, including an exploratory interview and a questionnaire with a 70% response rate, the study shows that the Ministry of Higher Education, Scientific Research, and Innovation (MHESRI) prioritizes internationalization, offering students more mobility opportunities. The study concludes with recommendations for the Directorate of Cooperation and Partnership to better implement the strategic objectives of the Pact ESRI/HERI 2030, while suggesting further research on identifying Moroccan students in international mobility and exploring South-South cooperation in higher education.